REMOTE WORK AS A METHOD OF LABOR PROTECTION IN PERIODS OF PUBLIC HAZARD - Serghei CHUCHA (Supremația Dreptului, 2021)
The study made it possible to consider distance work as a event within the labor protection institute. The results of the study make it possible to make clarifications and additions to the existing scientific ideas about the genesis of this institution of labor law and labor legislation. The prerequisites for the modernization of the legal regulation of distance work are revealed: the actual and widespread emergence of the corresponding economic relations; development of technological conditions for widespread use of remote work; adoption and approbation of legislation allowing remote registration of the emergence, change and termination of labor relations. The improvement of legislation took place in the conditions of self-isolation caused by the coronavirus pandemic, in the conditions of the forced digitalization of public relations, in the conditions of the constitution of social partnership in the world of work and the intensification of the application of its principles and mechanism in the practice of rule-making. Prospects for the legal regulation of distance work as an institution are associated with its extension to all categories of the precariat, as well as to all cases of the use of dependent labor. As a part of the labor protection institute, remote work has every chance of first spreading to new forms of dependent labor that have arisen and are emerging in a changing society in the process of preparing for the transition to the sixth technological order (platform employment, labor of economically dependent self-employed contractors, etc.). To do this, this institution should introduce the maximum possibility of differentiating the legal regulation of the relevant relations.